Textural characterization of gold in the Björkdal gold deposit, northern Sweden. - Westberg, Fredrik (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2021)
The Björkdal gold deposit is located in the eastern part of the Skellefte district, northern Sweden. Twenty thin sections from four production areas in the open pit and four drifts from the underground mine were analysed for mineral association and grain size distribution of gold. In addition, the texture of gold was investigated in order to find out how that affects the recovery of gold. The overall gold grain size distribution shows an interval from very fine-grained (2 μm) to coarse grained(856 μm) while the overall median size is 7 μm. Gold from the Quartz Mountain production area displays the smallest median size of 4 μm, whereas gold from the sampled drifts at 340m- and 385m- level has the largest median size of 14 μm. Gold at grain boundary is the dominant textural mode of gold from all sampled locations and varies from 62% to 92%. This is followed by intergrown which ranges between 8% and 29%. Of the sulfides, pyrite, chalcopyrite and pyrrhotite are the most common. Galena and was also present in the samples. Gold is significantly and positively correlated with tellurium (Appendix 10.1.1), and weakly positive correlated to silver and mercury. Gold show a close association to bismuth-tellurides in the samples. Apart from native gold, which is the dominant mineral phase of gold, two additional gold-bearing tellurium minerals were detected with SEM-EDS, a Au-Te-mineral and a Ag-Au-Te-mineral. One additional bismuth-telluride mineral aside from the most commonly occurring tsumoite (BiTe) was also detected with SEM, with a elemental composition of Bi-Te-S. Liberated gold in the tailings was optically identified in two thick sections, TB1-02feb-1 and TB1-07feb-1 (Fig. 32A and B), where the flotation circuit failed to float the free gold. One grain of gold was also identified intergrown with bismuth-telluride as an inclusion in silicate (Fig. 33), where the flotation properties of the larger silicate grain likely dominated in the flotation process. This thesis highlights the importance of further quantitative ...